Careers in architecture and construction - Sheen, Barbara (Exploring careers (ReferencePoint Press), 2016)
Comments from people in the industry, current statistics and forecasts, and realistic descriptions provide a useful look at architecture and construction jobs ranging from electricians to landscape architects to surveyors.